Evasão discente no ensino superior: estudo de caso na Universidade do Estado de Mato Grosso (UNEMAT) - Campus de Sinop - Goetz, Jackson Éder (2020)
School dropout is a complex phenomenon that has aroused the interest of researchers in terms of its occurrence in higher education. Their understanding is related to academic, institutional, social and economic elements. Thus, the concept of evasion was considered to be the student's departure from the course without having completed it, when the student disconnects from the higher education course in different situations such as abandonment (stops enrolling), withdrawal ( official), transfer, or option (change of course), exclusion by institutional rule, as defined by the Special Commission for the Study of Evasion by the Secretariat of Higher Education / Ministry of Education and Sport (SESU / MEC, 1996). From the studies proposed here, it is intended to know the main factors that influence the dropout of academics in the undergraduate courses of the State University of Mato Grosso Sinop campus in 2018. The research was characterized as descriptive with a qualitative and quantitative approach, ex post-facto. The universe of research consisted of 445 students dropped out of undergraduate courses at the State University of Mato Grosso, Sinop campus in 2018 and the sample was the return rate of the questionnaires sent on-line to the dropped-out students, which corresponded to 23, 37% of the universe, which represents a total of 104 participants. In general, in the opinion of academics, factors related to the difficulty of reconciling professional life with studies, followed by vocational, financial, and teaching methodology issues were considered the factors that most influenced academics to drop out. With these results, we can consider that the phenomenon of evasion is not only the responsibility of academics and must be shared by the institution with the development of external and internal actions to minimize its occurrence.